Variations of nutcracker phenomenon: A cadaveric and computed tomography angiographic study - Anisha Nautiyal; Deepika Sharma; Anjali Sharan; Piyush Kumar; Swati Saxena; Rajesh Maurya; Sonam Maheshwari; Jolly Agarwal; M K Pant (Wolters Kluwer Medknow Publications, 2023)
Introduction: The nutcracker phenomenon (NCP) (or the left renal vein [LRV] entrapment) focuses on the constriction of the LRV. It occurs commonly between the abdominal aorta (AA) and the superior mesenteric artery. The resulting clinical manifestation of this phenomenon is known as the nutcracker syndrome (NCS). Three types of this phenomenon have been reported: anterior, posterior, and mixed. NCP is a rare finding as reported by various authors. The aim of this study is to know the prevalence of NCP in the population of Uttarakhand, India. Methodology: The study was conducted to understand the tributaries of the renal veins and any variations in their pattern via 160-slice computed tomography (CT) angiography. CT angiographies were retrospectively studied to study the renal vasculature. A total of 14 renal veins which included four accessory renal veins (aRVs) (one left and three right) were analyzed from cadaveric dissection and 44 CT films were included (36 males and eight females) with 98 renal veins which included 10 aRVs (three left and seven right). Results: The current study was done on 49 cases (five cadavers and 44 CT angiography), in which a 10.2% prevalence of NCP was recorded. All were variants of mixed types of NCP. Conclusion: Although the NCP and NCS are rare occurrences, it has been determined that it was possibly underdiagnosed due to a lack of the proper advanced imaging and diagnostic modalities. Hence, it led to the undertreatment of the same. With recent development in diagnostic modalities such as multidetector CT, CT angiography, magnetic resonance angiography, etc., there has been a rise in diagnosis of NCP and NCS, thus resulting in increased prevalence.